1997
DOI: 10.1021/jo970641l
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrol in Intermolecular Dirhodium(II)-Catalyzed Carbonyl Ylide Formation and Reactions. Dioxolanes and Dihydrofurans

Abstract: Ethyl diazoacetate undergoes dirhodium(II)-catalyzed reactions with aryl aldehydes to form 1,3-dioxolanes as mixtures of diastereoisomers in good yields. Carbonyl ylides are reaction intermediates. Catalyst dependent diastereocontrol is observed for reactions with p-nitrobenzaldehyde, but not for those with p-anisaldehyde or benzaldehyde, so that at least with transformations involving p-nitrobenzaldehyde a metal-stabilized ylide is responsible for product formation. Higher yields are obtained with catalysis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…The rhodium(II)-catalyzed decomposition of ethyl diazoacetate in the presence of aldehydes furnished dioxolanes (by means of 1,3-dipolar cycloaddition of the carbonyl ylide intermediate with a second equivalent of aldehyde) and did not produce oxiranes. 5 Despite the commonality and selectivity (vide infra) of rhodium(II) acetate catalyzed reactions of diazo carbonyl compounds, they were not found to produce the oxirane ring systems until the recent report by Doyle 6 and followed by Davies. 7 In an alternative route, Aggarwal delineated a useful method 8 for the formation of oxirane by intercepting the metal carbene with alkyl sulfide.…”
mentioning
confidence: 99%
“…The rhodium(II)-catalyzed decomposition of ethyl diazoacetate in the presence of aldehydes furnished dioxolanes (by means of 1,3-dipolar cycloaddition of the carbonyl ylide intermediate with a second equivalent of aldehyde) and did not produce oxiranes. 5 Despite the commonality and selectivity (vide infra) of rhodium(II) acetate catalyzed reactions of diazo carbonyl compounds, they were not found to produce the oxirane ring systems until the recent report by Doyle 6 and followed by Davies. 7 In an alternative route, Aggarwal delineated a useful method 8 for the formation of oxirane by intercepting the metal carbene with alkyl sulfide.…”
mentioning
confidence: 99%
“…Treatment of a composite of p-anisaldehyde and a catalytic amount of Rh 2 (OAc) 4 with ethyl diazoacetate resulted in the formation of two carbonyl ylide cycloaddition products, identified as 279 and 280, out of the four possible diastereomers in ,15% yield (Scheme 85). 123 Higher conversions were achieved with catalysis by dirhodium(II) caprolactamate, Rh 2 (cap) 4 (52%), but the same ratio of 279/ 280 did not change from 52:48. With p-nitrobenzaldehyde, all four isomers were obtained with different ratios of products based on the catalyst variations.…”
Section: Intermolecular Carbonyl Ylidesmentioning
confidence: 94%
“…An alcoholic oxonium ylide may react with other nucleophilic components such as aldehyde to form nucleophilic addition products [18][19][20][21][22][23], or perform a rapid 1,2-hydrogen shift reaction in the absence of nucleophilic components [14,15,18,19,24,25]. All these reactions can proceed directly through Rh(II) complexassociated oxonium ylides or through free oxonium ylides derived from Rh(II) complex-associated ylides via direct decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…All these reactions can proceed directly through Rh(II) complexassociated oxonium ylides or through free oxonium ylides derived from Rh(II) complex-associated ylides via direct decomposition. Although oxonium ylide reactions with nucleophilic components were long believed to proceed through the free oxonium ylide [26][27][28], experimental evidence suggested that the nucleophilic addition of oxonium ylides generated by catalytic diazo compound decomposition proceed via Rh(II) complexassociated oxonium ylides instead of free oxonium ylides [18][19][20][21][22][23] …”
Section: Introductionmentioning
confidence: 99%